2010
DOI: 10.2174/1874192401004010240
|View full text |Cite
|
Sign up to set email alerts
|

Glycoxidative Stress and Cardiovascular Complications in Experimentally-Induced Diabetes: Effects of Antioxidant Treatment

Abstract: Diabetes mellitus (DM) is a common metabolic disease, representing a serious risk factor for the development of cardiovascular complications, such as coronary heart disease, peripheral arterial disease and hypertension. Oxidative stress (OS), a feature of DM, is defined as an increase in the steady-state levels of reactive oxygen species (ROS) and may occur as a result of increased free radical generation and/or decreased anti-oxidant defense mechanisms. Increasing evidence indicates that hyperglycemia is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 199 publications
(329 reference statements)
3
67
0
8
Order By: Relevance
“…Advanced glycation endproducts (AGEs) play an important role in the decrease of vascular distensibility. The biochemical production of AGEs has been shown to be increased in DM, because of the chronic oxidative stress caused by hyperglycemia (32). In the current study, vascular impairment observed in the DAP associated with DM was not limited to the arterial wall.…”
Section: Discussionsupporting
confidence: 45%
“…Advanced glycation endproducts (AGEs) play an important role in the decrease of vascular distensibility. The biochemical production of AGEs has been shown to be increased in DM, because of the chronic oxidative stress caused by hyperglycemia (32). In the current study, vascular impairment observed in the DAP associated with DM was not limited to the arterial wall.…”
Section: Discussionsupporting
confidence: 45%
“…Oxidative stress plays a pivotal role for the development of DM which increases complications with increased free radical formation (Karasu, 2010). Free radicals react with Polyunsaturated Fatty Acids (PUFA) of lipid membrane and cause lipid peroxidation (Barrera, 2012).…”
Section: Science Publicationsmentioning
confidence: 99%
“…[80] Unfortunately, blood chemistry of diabetic patients (uncontrolled hyperglycemia) may exhibit high serum advanced glycation end products, free radicals, metabolites of abnormal metabolism of carbohydrates and lipids (due to insulin lack), high serum cholesterol, high serum LDL and others. [80] Based on that, non-specific serum clearance induced by Al-hijamah may protect against and prevent further progression of some long-term complications of diabetes mellitus. Al-hijamah may benefit diabetic patients; prolong disease-free survival and offer better treatment outcomes.…”
Section: Therapeutic Benefits Of Al-hijamah For Diabetic and Stroke Pmentioning
confidence: 99%